The macroeconomic impact of economic uncertainty and financial shocks under low and high financial stress - Balcilar, Mehmet; Ozdemir, Zeynel Abidin; Ozdemir, Huseyin; Aygun, Gurcan; Wohar, Mark E. (Elsevier Science Inc, 2022)
External financial frictions might increase the severity of economic uncertainty shocks. We analyze the impact of aggregate uncertainty and financial condition shocks using a threshold vector autoregressive (TVAR) model with stochastic volatility during distinct US financial stress regimes. We further examine the international spillover of the US financial shock. Our results show that the peak contraction in euro area industrial production due to uncertainty shocks during a financial crisis is nearly-four times larger than the peak contraction during normal times. The US financial shocks have an influential asymmetric spillover effect on the euro area. Furthermore, the estimates reveal that the European Central Bank (ECB) is more cautious in implementing a monetary policy against uncertainty shocks while adopting hawkish monetary policies against financial shocks. In contrast, the Fed adopts a more hawkish monetary policy during heightened uncertainty, whereas it acts more steadily when financial stress rises in the economy.
Keywords: Economic uncertainty; Financial conditions; Regime switching; Spillover; US; Euro area